2014
DOI: 10.1007/s00436-014-4045-z
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus spp. in central Kenya: a different story

Abstract: Research on cystic echinococcosis (CE) has a long history in Kenya, but has mainly concentrated on two discrete areas, Turkana and Maasailand, which are known to be foci of human CE in Africa. Here, we report on a survey for CE in livestock from central to northeastern Kenya, from where no previous data are available. A total of 7,831 livestock carcasses were surveyed. CE prevalence was 1.92% in cattle (n = 4,595), 6.94% in camels (n = 216), 0.37% in goats (n = 2,955) and 4.62% in sheep (n = 65). Identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 16 publications
(21 reference statements)
1
35
2
Order By: Relevance
“…CE prevalence in camels is extremely high in northwestern Kenya, much less so in northeastern Kenya, eastern Ethiopia and Somalia (Table S12), for reasons unknown. In Kenya, the majority of camel cysts belonged to G6/7, but fertile cysts of E. granulosus (G1e3) were also present at lower numbers Mbaya et al, 2014); the reverse situation was found in eastern Ethiopia . There are no prevalence data for pigs in eastern Africa, except for two older studies with negative results from Ethiopia (Table S11).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 91%
“…CE prevalence in camels is extremely high in northwestern Kenya, much less so in northeastern Kenya, eastern Ethiopia and Somalia (Table S12), for reasons unknown. In Kenya, the majority of camel cysts belonged to G6/7, but fertile cysts of E. granulosus (G1e3) were also present at lower numbers Mbaya et al, 2014); the reverse situation was found in eastern Ethiopia . There are no prevalence data for pigs in eastern Africa, except for two older studies with negative results from Ethiopia (Table S11).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 91%
“…Elsewhere, it seems to be widespread, but usually rare (Cardona and Carmena, 2013). A small number of infections have been molecularly identified from cattle in Sudan (Dinkel et al, 2004;Omer et al, 2010), Kenya (Mbaya et al, 2014), South Africa (Mogoye et al, 2013), Brazil (de la Rue et al, 2006, Italy (Busi et al, 2007) and most recently in France (Grenouillet et al, 2014), cattle and buffaloes in India (Zhang et al, 1999), goats and sheep in Kenya (Mbaya et al, 2014), and pigs in Kenya and India (Dinkel et al, 2004;Pednekar et al, 2009). A case of monkey infection with E. ortleppi has been reported from Vietnam (Plesker et al, 2009), and a captive deer imported from France into the UK was found infected (Boufana et al, 2012).…”
Section: Echinococcus Ortleppimentioning
confidence: 99%
“…In countries with large numbers of camels, hydatidosis is also reported in these animals. According to these results, the prevalence of hydatidosis was found to be 7.45-70% in Iran [13] , 5.3% in Oman [14] , 2.53% in Egypt [15] , 6.86% in Saudi Arabia [16] , 8.8% in Jordan [17] , and 6.94% in Kenya [18] . In Central Asian camels, hydatic cysts have high viability and fertility rates [12] .…”
Section: Discussionmentioning
confidence: 99%